Return to sports after unilateral medial opening wedge high tibial osteotomy in highly active patients: Analysis of factors affecting functional recovery - Hiroshi Nakayama; Ryo Kanto; Shintaro Onishi; Takuya Iseki; Yoshitaka Nakao; Toshiya Tachibana; Kenta Amai; Shinichi Yoshiya; Tomoya Iseki (Journal of Experimental Orthopaedics)
Abstract Purpose The purpose of this study was to examine the outcomes following opening‐wedge high tibial osteotomy (HTO) focusing on return to sports in a consecutive series of highly active patients who underwent a unilateral osteotomy procedure. Methods Sixty‐three consecutive patients with preoperative Tegner's activity score of five or more who underwent unilateral HTO for varus osteoarthritic knees were included in this study. The clinical results were evaluated using the Knee Injury and Osteoarthritis Outcome Score (KOOS) and the International Knee Documentation Committee (IKDC) Subjective Score. In radiological assessment, the following parameters were measured in full‐length weight‐bearing radiographs both pre‐ and postoperatively; mechanical tibiofemoral angle (mTFA), mechanical medial proximal tibial angle (mMPTA) and joint‐line convergence angle. As regard postoperative functional recovery, inability to return to sports activities and reduction in the activity level on the Tegner scale were considered as failure to return to sports. Potential prognostic factors examined with logistic regression analysis were as follows: age ≥ 70, body mass index > 25, postoperative mTFA > 3° valgus or <0° varus, postoperative mMPTA > 90°, opening gap > 10 mm and Kellgren–Laurence classification (KL) grade 4. Results At 2 years after surgery, the KOOS and the IKDC score improved from 231 to 437 and from 34 to 72, respectively, with significant improvements in both scores. As for functional recovery, 50 patients (79.4%) could return to high‐impact sports activities at the presymptomatic level with a mean time period of 8.0 months. Statistical analysis of the prognostic factors showed that postoperative mTFA > 3° valgus, opening gap >10 mm and KL grade 4 were the factors significantly affecting the postoperative return to sports. Conclusions Presence of postoperative mTFA > 3° valgus, opening gap >10 mm and KL grade 4 were identified as risk factors impairing postoperative return to high‐impact sports. Level of Evidence Level Ⅳ.